PENANAMAN KARAKTER MANDIRI DAN TANGGUNG JAWAB MELALUI PROGRAM PENGABDIAN SANTRI DI PESANTREN ISLAM AL IRSYAD TENGARAN KABUPATEN SEMARANG - Muhamad Arifin Siregar; Winarno Winarno (STAI Asy-Syukriyyah, 2024)
This study aims to determine the description, implementation and evaluation of the student service program (khidmah) at Al Irsyad Islamic Boarding School in instilling independent and responsible characters. This research was conducted using descriptive qualitative method by: documentation, interviews and observations. The subjects are student who graduated from Aliyah level in 2022 and 2023. The results of the study include: [1] The cultivation of independent and responsible characters is realized through inauguration in the pesantren mission and the basis for organizing service programs, daily routine assignments, incidental activities, exemplary, as well as training and coaching. [2] The implementation is carried out by: debriefing khidmah candidates, giving positions and job descriptions, designing activities and budgets, dealing with solving santri problems, giving khidmah pocket money, exemplary, social interaction, preaching and taking part in the community. [3] The evaluation results still found obstacles: limited experience of khidmah students, initial adaptation to service, environmental influences, and parental interference. Solutions taken: strengthening the knowledge and skills, mentoring ustadz, preparing SOP, emphasizing the authority of santri khidmah, providing education and assistance in handling problem students, motivation and routine coaching.